Penyuluhan Sumber Air Minum Sehat Untuk Lansia Di Klinik Azzahra - Marthia Ikhlasiah (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
The purpose of community service activities is Counseling on Healthy Drinking Water Sources for the Elderly at Azzahra Clinic. This study uses descriptive research methods related to this Research Method The research method used is observational using a cross sectional design because all variables are measured at the same time. The purpose of this study design was to examine the level of fluid adequacy in the elderly compared to the Daily Value of Nutrition. The results of this study Many restrictions are used to determine a person, including the elderly, one of which is when entering the age over the age of 55 years Considering various problems of the elderly, the nutritional needs of the elderly are different from the nutritional needs of adults. Increasing age, the less nutritional needs of the elderly. Generally, energy needs are decreasing, while the need for some vitamins and minerals is more. The nutritional needs of the elderly men are different from those of the elderly women